Nutritional status affects incidence of pneumonia in underfives - Wicaksono, Henry (Folia Medica Indonesiana, 2016)
Pneumonia is an acute infection disease which remains the main killer of children under 5 years old worldwide. Based on Unicef's report, 17% of all children death is caused by pneumonia. Indonesia was in 10th position of the highest incidence of pneumonia and diarrhea which caused the death of children under 5 years old in 2013. In Gane Luar Public Health Center, there were at least 3 patients with pneumonia every month during 2014. The risk factors are less exclusive breastfeeding, malnutrition, low birth weight, less coverage of measles vaccine, indoor air pollution, and the high level of occupation density. The purpose of this research was to determine the relationship between exclusive breastfeeding, nutrition status, the type of house flooring, and pneumonia incidence in children under 5 in working area of Gane Luar Public Health Center, South Halmahera. A case control study was conducted to each 25 samples of case and control which were collected by simple random sampling technique during July-December 2014. Data were collected through a questionnaire using interview method, observation, and physical examination, and then it's analyzed by Regression Logistic, Chi Square, and Odds ratio to check for strength of association between variables at 95% confidence level. The results indicated that nutrition status was significantly related to Pneumonia incidence (p = 0.019 ; OR 3.795), however exclusive breastfeeding (p = 0.29) and type of house flooring (p = 0.086) weren't. In conclusion, the nutrition status was significantly related to the incidence of Pneumonia in working area of Gane Luar Public Health Center.